Spatial distribution of ectomycorrhizal and saprophytic fungi in relation with Shorea leprosula Miq. seedling survival in dipterocarp forest - Chaidir, Riri Rimbun Anggih (2016)
A central question in community ecology and conservation of highly diverse tropical forests concerns the control of the ability of tree species to coexist. This study explores the possible feedback mechanisms that control Shorea leprosula seedling regenerations and survival. This study also proposes a model of asymmetric ectomycorrhizal (EM) positive feedbacks that relies on the assumption of a niche differentiation between EM fungi (EMf) linked to seedlings and EMf linked to EM canopy trees. This study conducted on a deductive basis of how the mecanisms involved might be supported by the distributions of S. leprosula seedlings after a masting event, the percentage of seedling ectomycorrhization and the distributions of saplings below 1 cm diameter that established during previous masting events. Two hypotheses were considered. The first is that the distributions of ectomycorrhizas give benefits to S. leprosula seedlings survival correspond to the presence of ectomycorrhizal networks associated to ectomycorrhizal canopy trees. The second is that S. leprosula seedlings survival benefits from ectomycorhizal associations that are independent from the distribution of ectomycorrhizal canopy trees and facilitated by the presence of large saprophytic fungi. Spatial variations of S. leprosula seedlings ectomycorrhizal rate didn’t support with the first hypothesis. Seedlings ectomycorrhizal rates only increased near to parent trees but not near other ectomycorrhizal canopy trees. Similarly, S. leprosula saplings distributions believed to witness seedling survival from previous masting events were either not correlated or negatively correlated with the distribution of ectomycorrhizal canopy trees. Whereas, the revelation of putative mat-forming and foraging ectomycorrhizal fungi in association with saprophytic fungi agreed with the second hypothesis. These traits, observed for the first time in a Southeast Asian lowland rainforests concord with a possible ecological niche differentiation between ectomycorrhizal fungi linked to canopy trees and ectomycorrhizal fungi succeeding to saprophytic fungi and possibly contributing to S. leprosula seedling survival.